Interacciones medicamentosas potenciales en el servicio de neurología del hospital nacional edgardo rebagliati martins, julio - diciembre 2009 - Sánchez Muguerza, Leidy Verónica (2010)
At present there is lack of more frequent interactions, which may lead to therapeutic failure and thus affect the quality of life of patients. This has motivated the study of Potential Drug Interactions in the Service of Neurology HNERM, July-December 2009. We used the literature-analytical method used as the main source is the Drug Interaction Facts 2008, to establish the clinical significance. Where it was observed that 63% of prescriptions had potential drug interactions. We also proceeded to the characterization of drug interactions in pharmacokinetic and pharmacodynamic, pharmacokinetic interactions be presented at the highest frequency (80.5%), and 50.5% of drug interactions occurred in male patients. Finally it was determined that the most common potential drug interactions were: Phenytoin-Diazepam (8%), phenytoin, ranitidine (6.6%), and phenytoin the drug they most often for drug interactions with 19.8%. The highest percentage of potential drug interactions corresponded to the clinical significance 4 and 5 with 41.2 % and 22 % respectively